Differential Diagnosis of Transient Amnesia. Issue 5892 (8th December 1973) - Croft, P. B.; Heathfield, K. W. G.; Swash, M.
Abstract : In a group of 39 consecutive patients attending neurological clinics with transient amnesia patients with transient global amnesia formed the largest group; others suffered from epilepsy, migraine, temporal lobe encephalitis, or psychogenic fugues. In most cases the clinical features suggested the aetiology, but an electroencephalogram recorded as soon after the attack as possible may help in distinguishing amnesia due to temporal lobe epilepsy.